Illusions perdues = Lost illusions [videorecording (DVD)] - Giannoli, Xavier, 1972-; Giannoli, Xavier, 1972-; Fieschi, Jacques, 1948-; Beaucarne, Christophe; Larroque, Pierre-Jean; Voisin, Benjamin, 1996-; France, Cécile de, 1975-; Lacoste, Vincent, 1993-; Dewaels, Salomé; Balibar, Jeanne, 1968-; Marcon, André; Lencquesaing, Louis-Dominique de; et al. (Music Box Films, 2022)
An aspiring poet joins a cynical team of journalists in nineteenth-century Paris. When he agrees to write rave reviews for bribes, achieving material success at the expense of his conscience, and soon discovers that the written word can be an instrument of both beauty and deceit.